A study of variable energy blast waves in magnetogas dynamics - Ray, Amit K (Journal of Experimental Sciences, 2012)
In this paper, we have studied the propagation of shock waves in a gaseous medium in presence of magnetic field. The flow fields being spherical, cylindrical or planar, respectively. Salient differences between the instantaneous energy and the variable energy are also presented.